Access to Credit and Loan Repayment by Households of Non-Farmers in Nigeria: New Evidence from Binary Logit Regression - Obed I. Ojonta; Jonathan E. Ogbuabor; Anthony Orji; Onyinye I. Anthony-Orji; Ndubuisi Chukwu; Emmanuel T. Ideba (Managing Global Transitions)
Access to credit is the desire of every developing economy as well as a coping strategy in starting up and expanding businesses. Hence, this study critically examines how access to credit responds to loan repayment by households of non-farmers in Nigeria. To achieve this purpose, some important variables like spending on transport, other business costs, salaries/wages and rent were included in the model. Other variables in the model include age and location for the households of non-farmers. The study shows that loan repayment by households of non-farmers and their place of residence are significant drivers of access to finance in  Nigeria while other characteristics of non-farmers such as spending on transport, other business costs, salaries/wages, rent and age are muted throughout.